A preliminary study of psychological pain among patients attending the dental clinic of a tertiary hospital - A. O. Coker; O. O. Onigbinde; M. E. Sorunke; A. O. Awotile; O. B. Ogunbanjo; V. O. Ogunbanjo (Nigerian Dental Association, 2012)
Objective: Dental practitioners frequently encounter individuals who suffer from psychological pain at the dental clinics. Most dentists do not have the training or the instrument to recognise and manage psychological pain associated with dental treatment. This study was carried out to determine the level of psychological pain among dental patients visiting the dental clinic of the Lagos State University Teaching Hospital, Ikeja, Lagos, Nigeria. Method: One hundred and twenty five patients who attended the dental clinic of the Lagos State University Teaching Hospital, Ikeja, Lagos, Nigeria were invited to take part in the study. They completed a sociodemographic questionnaire, Psychache Scale (PAS) and the Hamilton Anxiety Rating Scale (HARS) in order to determine their levels of psychological pain and anxiety. Result: Of the total respondents, 43% were males and 57% females, mean age 30.2 years (SD=10.7, ranging from 15-80), 74.2% were married and 22.5% single. With regards to psychological pain and anxiety, 31.9% scored high in the PAS, indicating probable psychological pain while 25.8%, 19.4% and 54.8% were detected to suffer from mild, moderate and severe anxiety as detected by HARS. Conclusion: The finding from this study demonstrated that Nigerian dental patients also suffer from psychological pain and various degrees of dental anxiety. Therefore there is a need for Nigerian dental surgeons to acquire some knowledge of mental health in order to recognise these psychopathologies among their patients.